Victorian literature and the anorexic body - Silver, Anna Krugovoy (Cambridge studies in nineteenth-century literature and culture ;, 2002)
"Anna Krugovoy Silver examines the ways nineteenth-century British writers used physical states of the female body - hunger, appetite, fat, and slenderness - in the creation of female characters. Silver argues that anorexia nervosa, first diagnosed in 1873, serves as a paradigm for the cultural ideal of middle-class womanhood in Victorian Britain. In addition, Silver relates these literary expressions to the representation of women's bodies in the conduct books, beauty manuals, and other non-fiction prose of the period, contending that women "performed" their gender and class alliances through the slender body. Silver discusses a wide range of writers including Charlotte Bronte, Christina Rossetti, Charles Dickens, Bram Stoker, and Lewis Carroll to show that mainstream models of middle-class Victorian womanhood share important qualities with the beliefs or behaviors of the anorexic girl or woman."--Jacket